2021
DOI: 10.1021/acs.jafc.1c02659
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Bioactivity of the Novel Lasso Peptide Microcin Y

Abstract: Lasso peptides, a class of ribosomally synthesized and post-translationally modified peptides (RiPPs) secreted by bacteria, have antimicrobial activity. Here, a novel lasso peptide, microcin Y (MccY), was discovered and characterized. The gene cluster for MccY synthesis was cloned for expression in Escherichia coli. This peptide was purified by HPLC and characterized by Q-TOF. MIC assays showed that some Bacillus, Staphylococcus, Pseudomonas, Shigella, and Salmonella strains were sensitive to MccY. Interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(72 citation statements)
references
References 42 publications
(70 reference statements)
1
71
0
Order By: Relevance
“…The bioactivity of ubonodin, and indeed any compound with an intracellular target, is a product of its ability to first access and then bind its target. Previous studies have shown that cellular uptake is required for lasso peptides with RNAP-inhibiting activity to be bioactive (Cheung-Lee et al, 2019; Li et al, 2021; Metelev et al, 2017; Salomón and Farías, 1993). In all cases where the lasso peptide OM receptor has been identified, the receptors are TonB-dependent transporters (TBDTs), a ubiquitous class of bacterial OM proteins that import essential trace nutrients like iron from the environment ( Figure 3A ) (Krewulak and Vogel, 2011; Noinaj et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bioactivity of ubonodin, and indeed any compound with an intracellular target, is a product of its ability to first access and then bind its target. Previous studies have shown that cellular uptake is required for lasso peptides with RNAP-inhibiting activity to be bioactive (Cheung-Lee et al, 2019; Li et al, 2021; Metelev et al, 2017; Salomón and Farías, 1993). In all cases where the lasso peptide OM receptor has been identified, the receptors are TonB-dependent transporters (TBDTs), a ubiquitous class of bacterial OM proteins that import essential trace nutrients like iron from the environment ( Figure 3A ) (Krewulak and Vogel, 2011; Noinaj et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Microcin J25 uses the E. coli TBDT FhuA for OM transport (Mathavan et al, 2014; Salomón and Farías, 1993). Klebsidin (Metelev et al, 2017) and microcin Y (Li et al, 2021) likewise use FhuA-like transporters. In these cases where the OM transporters were identified, the ability to readily isolate resistant mutants that have a mutation in the OM transporter or to predict a close homolog to E. coli FhuA was crucial to their identification.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these features have been reviewed [65], but will be described briefly here. Uptake is achieved through the FhuA [115,116] or OmpF [65,117] receptors.…”
Section: Class I Microcinsmentioning
confidence: 99%
“…For the only Class I microcin where the energetic means of uptake is known, MccJ25, the TonB-ExbBD system is used [107]. Identified inner membrane receptors are the transporters, SbmA [107, 116, 117] or YejABEF (ABC transporter) [118]. SbmA belongs to a proposed new class of secondary transporter [119].…”
Section: Uptake and Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation